A fluorescence turn-on probe for human (bovine) serum albumin based on the hydrolysis of a dioxaborine group promoted by proteins. Issue 48 (31st May 2017) - Sun, Qian; Wang, Weisi; Chen, Zhaoyang; Yao, Yuhua; Zhang, Weibing; Duan, Liping; Qian, Junhong
Abstract : A reaction-based florescence probe CBF for serum albumin (SA) was proposed by connecting a dioxaborine unit with environment-sensitive coumarin fluorophore. CBF exhibits high selectivity and sensitivity toward SA over other biologically relevant species and has potential of detecting SA in biosamples. Abstract : A fluorescence "off–on" probe CBF, constructed by incorporating a dioxaborine unit into a microenvironment-sensitive fluorophore, was developed for serum albumin (SA). Upon binding to SA, the dioxaborine group in CBF was hydrolyzed into β-diketonate, which triggered dramatic fluorescence enhancement (over 1000-fold) along with a remarkable blue-shift (∼100 nm). The bioimaging results suggested that more SA were taken in by cancer cells.